Religiosity As The Main Pillar of Character Education In Islamic Boarding School: A Study In Langkat District - Desfita, Vivi; Lubis, Saiful Akhyar; Rusman, Abdul Aziz (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study aims to describe the implementation model of character education based on the pillars of Islamic religiosity (Faith, Islam, and Ihsan) in Islamic boarding schools as a response to the moral and character crisis of adolescents in the modern era. This study focused on two locations, namely Jabal Rahmah Islamic Boarding School and Al-Habib Islamic Boarding School, with a multi-site qualitative approach. Data were collected through observation, in-depth interviews, documentation, and field notes, and analyzed using data reduction, presentation, and verification of findings techniques. The results of the study showed that both Islamic boarding schools instilled core character values ​​such as faith, piety, noble morals, responsibility, discipline, simplicity, and social concern, which were integrated into daily activities and learning curriculum. The methods used included role models, habituation, discussion, self-reflection, and spiritual guidance. The difference between the two Islamic boarding schools lies in the specific approach: Jabal Rahmah emphasizes more on curriculum integration and entrepreneurship programs, while Al-Habib focuses on self-development and partnerships with parents. In conclusion, character education based on the pillars of religiosity in Islamic boarding schools has proven effective in forming the personality of students who are noble and religious. However, its success is influenced by environmental support, leadership patterns, learning methods, and the involvement of families and the surrounding community. Sustainable synergy between educational actors is the key to strengthening the internalization of character values ​​as a whole.